Nano-based formulations of thymoquinone are new approaches for psoriasis treatment: a literature review - Modarresi Chahardehi, Amir; Ojaghi, Hamid Reza; Motedayyen, Hossein; Arefnezhad, Reza (Frontiers in Immunology, 2024)
Psoriasis, a persistent immune-mediated inflammatory skin condition, affects approximately 2-3% of the global population. Current treatments for psoriasis are fraught with limitations, including adverse effects, high costs, and diminishing efficacy over time. Thymoquinone (TQ), derived from Nigella sativa seeds, exhibits promising anti-inflammatory, antioxidant, and immunomodulatory properties that could prove beneficial in managing psoriasis. However, TQ's hydrophobic nature and poor bioavailability have hindered its usefulness as a therapeutic agent. Recent research has strategically addressed these challenges by developing nano-thymoquinone (nano-TQ) formulations to enhance delivery and efficacy in treating psoriasis. Preclinical studies employing mouse models have demonstrated that nano-TQ effectively mitigates inflammation, erythema, scaling, epidermal thickness, and cytokine levels in psoriatic lesions. Various nano-TQ formulations, including nanoemulsions, lipid vesicles, nanostructured lipid carriers, and ethosomes, have been explored to improve solubility, facilitate skin penetration, ensure sustained release, and achieve site-specific targeting. Although clinical trials are currently scarce, the outcomes from in vitro and animal models are promising. The potential co-delivery of nano-TQ with other anti-psoriatic agents also presents avenues for further investigation.